FEMINIST PERSPECTIVES IN THE SELECTED NOVELS OF SHASI DESHPANDE - A STUDY (International Journal of Food and Nutritional Sciences, 2021)
Shashi Deshpande has many symbols. In intellectual debates, she champions the cause of English as an Indian language and fights for the recognition of women as individuals. She speaks the truth soft but firmly, her words lingering long after she is gone. This article develops the true story of women representing themselves or all women in a way that is not the same as a man telling a woman's . It also highlights the opportunity for women to enlighten themselves and go beyond selfAneglect to spread their wings of faith. This study, based on selected novels by Shashi Deshpande,discusses complexities of maleAfemale relationships, particularly in the context of marriage, as well as the trauma of interrupted adolescence, referring to four novels by Shashi Deshpande, specifically. Dark Holds No Terrors (1980), The Winner of the Vine in That Long Silence A Matter of Time and Medicine in the Shadows, Penguin India (2000), On, Penguin describe what happens to men and women in marriage and then what they have, what they have become and what awaits them. These four novels describe the changing state of men and women after marriage and the changing nature of marital relationships. Focusing on the marital relationship, they attempt to explore the tradition by which a woman is shaped to fulfill her subordinate role in the family. Shashi Deshpande's novels also show how carefully she expresses the frustration and disappointment that women experience in their marital relationships . This implies that men and women must work together to create a mature and balanced gender relationship.Key words: Women struggle, assignment, Self-identity, confidence, freedom of women.